Factors That Can Promote the Green Entrepreneurial Intention of College Students: A Fuzzy Set Qualitative Comparative Analysis - Cai, Xinhai; Hussain, Shahid; Zhang, Yuying (Frontiers in Psychology, 2022)
Green entrepreneurship has a huge role in solving environmental degradation and social problems. As today’s youth are tomorrow’s entrepreneurs, enhancing their green entrepreneurial intention will contribute to the sustainable development of economy in the future. Research has examined the green entrepreneurial intention of college students based on self-efficacy, entrepreneurial creativity, entrepreneurial education, financial support, sustainable development values, and other influencing factors. However, these studies focus on the direct relationship between a single factor and the results of college students’ green entrepreneurial intention, ignoring the combination of multiple factors, and the relationship between each group of factors and the results of college students’ green entrepreneurial intention. Therefore, this study aimed to understand and analyze the influence of the complex relationship between multiple antecedents (entrepreneurial creativity, future self-continuity, green cognition, entrepreneurial culture, entrepreneurial education, and financial support) on college students’ green entrepreneurial intention from a comprehensive perspective. Based on 207 questionnaires collected from universities in the coastal cities of China, this study used the fuzzy set qualitative comparative analysis method for data analysis. The results showed three dominant paths of great significance to college students’ high green entrepreneurial intention: entrepreneurial creativity—green cognition—dominant path; entrepreneurial creativity—financial support—dominant path; and the future self-continuity—entrepreneurship culture—entrepreneurship education—dominant path. The results of this study can help university educators to plan courses on innovative thinking and green entrepreneurship to improve college students' entrepreneurial creativity and green cognitive ability.